The positivist inheritance turned into legalism - Altamirano Portocarrero, José C. (2007)
The inheritance of the positivism is shaped in the relevance that it has for it the principles of legality and legal certainty, if they were taken from the positivist perspective, it would not be possible to talk about legal right, whereas the work of the judge would be limited to the objective application of the law. Nevertheless, we cannot conceive these principles from a positivist perspective; we must study them keeping in mind the existing concepts of justice, conceived from a certain ideology, belief, custom, etc. Based on them, understand the values that incarnate and nourish the ordering, as well as the ordering itself.